Paleomagnetic data from sedimentary sequences on Bylot Island, Nunavut. ... : Données paléomagnétiques provenant de séquences sédimentaires, île Bylot, Nunavut. ... - Daniel Fortier; Coulombe, Stéphanie; Guillaume St-Onge; Guertin-Pasquier, Alexandre (Nordicana D, 2023)
This dataset presents a compilation of paleomagnetic records from glacigenic sedimentary sequences studied on Bylot Island (Nunavut). Discrete sediment samples were collected from three undisturbed stratigraphic sections (A, B, C) to constrain the age of the sediment and buried glacier ice preserved in the permafrost. Paleomagnetism is a relative dating technique based on the principle that changes in the Earth's magnetic field are preserved in rocks and sediments. Paleomagnetic measurements were carried out at the Paleomagnetism and Marine geology Laboratory at the Institut des sciences de la mer de Rimouski (ISMER, Rimouski, QC). ... : Ce jeu de donnée présente une compilation de données paléomagnétiques provenant de séquences sédimentaires glacigènes étudiées à l'île Bylot (Nunavut). Des échantillons discrets de sédiments ont été prélevés à partir de trois sections stratigraphiques non perturbées (A, B, C) afin de déterminer l'âge des sédiments et de la glace de glacier enfouie dans le pergélisol. Le paléomagnétisme est une technique de datation relative qui est basée l'enregistrement des variations du champ magnétique terrestre dans les roches et les sédiments. Les analyses ont été réalisées au Laboratoire de recherche en Paléomagnétisme et Géologie marine de l'Institut des sciences de la mer de Rimouski (ISMER, Rimouski, QC). ...